ANALISIS KEUNGGULAN KOMPETITIF PRODUK PEWARNA ALAMI BERDASARKAN STRATEGI HARGA JUAL - Cahyari, Ratri; Wadji, Farid; Seryawan, Anton Agus (Jurnal Manajemen Dayasaing, 2015)
The purpose of this study to evaluate the selling price of natural dyes manufacturerand make a pricing strategy y results of this study found that the cost components thatare not taken into account in the accounts namely the cost of goods sold resulted inthe selling price of the company could not achieve the purpose of profit. The resultsof this study showed that the company’s success is determined by pricing strategies.Start using the product introduction phase skim milk pricing strategy. The growth stageof the product using the product line pricing strategy, global product pricing strategy,and a captive product pricing strategy. While at the stage of maturity of the productusing the appropriate defense strategy, geographic strategy criteria of price, rebatebonusstrategy, and strategy to survive. At the stage of decline in product strategy pricereductions and price increases strategy.